A reforma tributária e os seus reflexos no Imposto sobre Transmissão Causa Mortis e Doação ITCMD - Gonçalves, Isabella Paschoal (2024)
This paper seeks to analyze the main effects of the Tax Reform on the Tax on Inheritance and Donation – ("ITCMD"), considering the main changes arising from Constitutional Amendment nº 132 of 2023 and some of the main discussions and controversies that are behind these changes. The objective of this work is to analyze these changes and, as a consequence, their impacts